1993
DOI: 10.1039/ft9938903395
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of thermal aggregation of bovine β-lactoglobulin A

Abstract: On heating, bovine 8-lactoglobulin A (8-lg A) dimers dissociate and then aggregate. The extent of aggregation of 8-19 A after a heat-quench treatment was studied quantitatively using photon correlation spectroscopy (PCS) ; circular dichroism (CD) spectroscopy was also carried out on heated solutions of 8-1s A to examine changes in the secondary and tertiary structure of t h e protein. In pH 7.0 solution the protein underwent a change in tertiary structure at 67 "C; by contrast, the secondary structure, contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
77
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 61 publications
18
77
1
2
Order By: Relevance
“…The protein contains five cysteine residues per monomer, one free and four involved in two disulfide bridges. Native b-LG has 40-50% b-sheet, 10-15% a-helix and 40% random coil structure (Griffin, Griffin, Martin, & Price, 1993;Qi et al, 1997), data supported by Xray crystal structure . It can be obtained in large quantities and high purity by membrane filtration processes (Maubois, Pierre, Fauquant, & Piot, 1987).…”
Section: Introductionmentioning
confidence: 65%
“…The protein contains five cysteine residues per monomer, one free and four involved in two disulfide bridges. Native b-LG has 40-50% b-sheet, 10-15% a-helix and 40% random coil structure (Griffin, Griffin, Martin, & Price, 1993;Qi et al, 1997), data supported by Xray crystal structure . It can be obtained in large quantities and high purity by membrane filtration processes (Maubois, Pierre, Fauquant, & Piot, 1987).…”
Section: Introductionmentioning
confidence: 65%
“…For example, when bovine ␤-lactoglobulin A, a ␤-sheet-rich protein, is thermally denatured, the effect on the secondary structure (as measured by CD) is very small (36). It has been proposed that the aggregation/misfolding of many proteins is associated with the formation of intermolecular ␤-sheet structures (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when bovine ␤-lactoglobulin A, a ␤-sheet-rich protein, is thermally denatured, the effect on the secondary structure (as measured by CD) is very small (36). It has been proposed that the aggregation/misfolding of many proteins is associated with the formation of intermolecular ␤-sheet structures (36,37). The relatively low temperature required to cause loss of binding activity of ␣210GPI and the inefficient folding of the ␣ subunit in vivo (with most of the newly synthesized ␣ subunit appearing as non-␣-Btx-binding aggregates) suggests that the ␣ subunit is susceptible to this form of misfolding.…”
Section: Discussionmentioning
confidence: 99%
“…However, when heated above 70 C whey proteins unfold, exposing reactive groups that are responsible for protein aggregation (Griffin, Griffin, Martin, & Price, 1993;Roefs & De Kruif, 1994;Sawyer, 1968;Verheul, Roefs, & de Kruifs, 1998) and emulsion instability (Çakir-Fuller, 2015;Dybowska, 2011;Euston et al, 2000;Hunt & Dalgleish, 1995;McClements, 2004;Surel et al, 2014). It has been shown that the heat stability of whey protein-stabilized emulsions is dependent on the concentration of native whey protein in the dispersing phase (Çakir-Fuller, 2015;Dybowska, 2011;Euston et al, 2000).…”
Section: Introductionmentioning
confidence: 97%